Analysis of Prevention and Treatment of Anastomotic Leakage after Sphincter-Preserving Surgery for Middle- and Low-Grade Rectal Cancer under Laparoscopy. (7th December 2022) - Yu, Jia-He; Huang, Xiang-Wu; Song, Yu-Cheng; Lin, Hui-Zhong; Zheng, Feng-Wu
Abstract : Background . Anastomotic leakage is one of the most serious complications that can occur after laparoscopic-assistedsphincter-preserving surgery for middle- and low-grade rectal cancer. Objectives . To explore the cause, prevention, and treatment of anastomotic leakage after sphincter-preserving surgery for middle- and low-grade rectal cancer under laparoscopy. Methods . The clinical data from patients with mid- and low-grade rectal cancer who underwent laparoscopic-assistedanus-preserving surgery in the anorectal surgery department of our hospital have been analyzed. Patients with a definite diagnosis, indications for laparoscopic surgery, and sphincter-preserving surgery were included in the analysis, and patients with a protective loop ileostomy and laparotomy were excluded. Results . Among the 126 patients with middle- and low-grade rectal cancer undergoing sphincter-preserving surgery under laparoscopy. There were 75 male patients and 51 female patients, ranging in age from 37 to 89 years old, with an average age of 60.2 ± 6.7. The distance from the lower edge of the rectal tumor to the anal edge was ≤10 cm. 6 developed anastomotic leakage after the operation (leakage rate of 4.7%). Moreover, turbid purulent fluid was drained from the abdominal drainage tube in three patients on the third and fourth days after the operation, and the abdominal drainage tube drained serous drainage in three more patients on the fifth and sixth days, with signs of peritonitis appearing locally. All patients received continuous flushing and negative pressure drainage with a self-made double cannula and symptomatic treatment, and all were cured and discharged. Conclusion . Many factors can cause anastomotic leakage after this operation, and adequate perioperative preparation, meticulous operation during surgery, and careful postoperative management are key factors in preventing it.